Serum cancer antigen 125 in patients with pleural effusions - How, Soon Hin; Liam, C K; Ab Rahman, Jamalludin; Chin, S P; Zal, A. B. (Malaysian Medical Association, 2006)
We studied the prevalence of raised serum CA125 in patients with pleural effusions and explored factors affecting its level. Sixty four patients with benign effusions and 36 patients with malignant effusions admitted to the University Malaya Medical Centre from May 2001 to January 2002 were included in the study. There were no significant differences in age, gender and ethnicity of the patients with benign and malignant effusions. There was also no difference in the frequency of the side of pleural effusion between the two groups but compared to benign effusions, a higher proportion of malignant effusions was moderate to large in size (66% versus 39%, p = 0.011). Serum CA125 levels were above 35U/dL in 83.3% and 78.1% of patients with malignant and benign effusions, respectively (p = 0.532). All patients with underlying malignancy and 95.3% of patients with benign effusions had pleural fluid CA125 levels above 35U/dL (p = 0.187). The median levels of CA125 were higher in the pleural fluid than in the serum in all aetiological groups. Higher serum CA125 levels were more likely to be found in patients with moderate to large effusions (p = 0.015), malignant effusions (p = 0.001) and in female patients (0.016). Serum CA125 level showed significant correlation with pleural fluid CA125 level (r = 0.532, p < 0.001) but not with pleural fluid total white blood cell count (r = -0.092, p = 0.362), red blood cell count (r = -0.082, p = 0.417) and lactate dehydrogenase level (r = 0.062, p = 0.541). We conclude that serum CA125 is commonly elevated in patients with benign and malignant pleural effusions.